Inequality in Good and Bad Times : A Cross-Country Approach - Hacibedel, Burcu (IMF Working Papers; Working Paper, 2019)
This paper provides evidence of a strong relationship between the short-term dynamics of growth and inequality in developing economies. We find that reductions in inequality during growth upswings are largely reversed during growth slowdowns. Using a new methodology (mediation analysis), we identify unemployment, and youth unemployment especially, as the main channel through which fluctuations in growth affect future dynamics in inequality. These findings suggest that both the quality of jobs created and labor market policies are important to ensure that growth outcomes are conducive to inequality reduction.